2015
DOI: 10.1007/s13131-015-0724-6
|View full text |Cite
|
Sign up to set email alerts
|

Burial fluxes and source apportionment of carbon in culture areas of Sanggou Bay over the past 200 years

Abstract: In this study, we assessed the burial fluxes and source appointment of different forms of carbon in core sediments collected from culture areas in the Sanggou Bay, and preliminarily analyzed the reasons for the greater proportion of inorganic carbon burial fluxes (BF TIC ). The average content of total carbon (TC) in the Sanggou Bay was 2.14%. Total organic carbon (TOC) accounted for a small proportion in TC, more than 65% of which derived from terrigenous organic carbon (C t ), and while the proportion of mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 29 publications
2
3
0
Order By: Relevance
“…In any case, this result directly confirms the important role of large-scale scallop farming in the accumulation of SOM [4,8,36]. Similar observations were also documented by Liu et al [19] and Zhou et al [87] in Sangou Bay and Daya Bay, China. Moreover, interestingly, it was also found that the scallop culture in this study seemed to promote the burial of terrestrial OC in the sediments of core H3 (Figure 6e), which may be related to the decomposition mode of SOM, e.g., priming effect, but the specific mechanism needs further research.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…In any case, this result directly confirms the important role of large-scale scallop farming in the accumulation of SOM [4,8,36]. Similar observations were also documented by Liu et al [19] and Zhou et al [87] in Sangou Bay and Daya Bay, China. Moreover, interestingly, it was also found that the scallop culture in this study seemed to promote the burial of terrestrial OC in the sediments of core H3 (Figure 6e), which may be related to the decomposition mode of SOM, e.g., priming effect, but the specific mechanism needs further research.…”
Section: Discussionsupporting
confidence: 86%
“…In this study, the sedimentation rates in the SFA, 0.88-0.90 cm yr −1 , were at a relatively high level, significantly higher than those observed in the central Bohai Sea (0.094-0.17 cm yr −1 ) and the coastal waters of the East China Sea (<0.2 cm yr −1 ), and comparable to those observed in other Chinese aquaculture areas along the west coastline of the Yellow Sea, e.g., Sanggou Bay (0.66 cm yr −1 ) and Jiaozhou Bay (0.64-1.74 cm yr −1 ) [19,[73][74][75][76][77][78].…”
Section: Effect Mechanism Of Scallop Farming On Som Dynamicssupporting
confidence: 83%
See 2 more Smart Citations
“…Marine aquaculture (mariculture) has rapidly expanded over the past two decades and currently provides an essential source of animal protein worldwide (Bouwman et al 2013). Intensive mariculture activities not only influence water quality and biodiversity, but also result in very high burial rates of organic matter in mariculture impacted areas (Liu et al 2015(Liu et al , 2016. Several studies demonstrated severe environmental and biological changes of coastal waters after long-term intensive mariculture activities (Duarte et al 2003;Li et al 2018a;Xu et al 2020a).…”
mentioning
confidence: 99%